Prenatal diagnosis of dextrocardia with complex congenital heart disease using Fetal Intelligent Navigation Echocardiography (FINE) and a literature review - Yeo, Lami (Fetal Diagn Ther, 2017)
Fetal dextrocardia is a type of cardiac malposition where the major axis from base to apex points to the right side. This condition is usually associated with a wide spectrum of complex cardiac defects. As a result, dextrocardia is conceptually difficult to understand and diagnose on prenatal ultrasound. The advantage of four-dimensional sonography with spatiotemporal image correlation (STIC) is that this modality can facilitate fetal cardiac examination. A novel method known as Fetal Intelligent Navigation Echocardiography (FINE) allows automatic generation of nine standard fetal echocardiography views in normal hearts by applying intelligent navigation technology to STIC volume datasets. In fetuses with congenital heart disease, FINE is also able to demonstrate abnormal cardiac anatomy and relationships when there is normal cardiac axis and position. However, this technology has never been applied to cases of cardiac malposition. We report herein for the first time, a case of fetal dextrocardia and situs solitus with complex congenital heart disease in which the FINE method was invaluable in diagnosing multiple abnormalities and defining complex anatomic relationships. We also review the literature on prenatal sonographic diagnosis of dextrocardia (with an emphasis on situs solitus), as well as tricuspid atresia with its associated cardiac features.